PRIYANKA CHOPRA’S HYBRID IDENTITY AS A PUBLIC FIGURE SEEN THROUGH HER INSTAGRAM POSTS - Wijaya, Clara Andita Dwi Putri (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
Fans from all across the world have taken notice of Priyanka Chopra as a public figure. Similar to many other celebrities, she regularly posts details about her personal and professional lives on social media. Because of her special place at the intersection of Indian and American society, Chopra’s Instagram posts represent her cultural identity. In analyzing how her hybrid identity as Indian and American is portrayed, this study examines her Instagram posts. The discussion, which uses postcolonial theory and the idea of hybrid identity, focuses on posts made between 2018 and 2024 when she married American musician Nick Jonas. According to this study, Chopra has a hybrid identity reflected in her appearances and the cultural events she participates in. She shows how she maintains her Indian roots while embracing American and Western cultural customs through her posts.